Demographic, Lifestyle, Job Factor for Mental Disorders: Descriptive Study among Port Logistic Terminal Employees at Tanjung Priok - Putri, Eka Cempaka; Situngkir, Decy; Sumartanto, Mukhlas (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: The results of work stress research in the port industry show work stress at the port has the strongest relationship with the mental workload, followed by role ambiguity and interpersonal conflict. However, in the port industry with hot, noisy working conditions, unclear age limits for workers, workers with various backgrounds triggering conflict, long working hours triggering not only stress, but anxiety and depression in workers, results in high absenteeism and hypertension cases in port workers. The aim of this research is see how demographic factors, lifestyle, and job factors contribute to the incidence of mental disorders problems in the port logistic industry. Methods: We carried out descriptive analysis for demographic aspects, lifestyle, and work factors with each component of mental disorders, namely stress, anxiety and depression. Design study for this research is cross-sectional. DASS 42 was an instrument for dependent variable. Data analysis was conducted with the Chi-square test to see the strength of the relationship between the two variables. The sample in this study was 201 with total sampling method. Result: Research results show that demographic factors do not have a strong relationship with mental disorders; lifestyle factors are the factors that have the strongest relationship with mental disorders, namely routine exercise and sleep duration. Work factors do not have a strong relationship with mental disorders at Port Logistic Terminal at Tanjung Priok. Conclusion: Regular exercise and sleeping more than 7 hours can reduce the frequency of mental disorders. Companies can focus on providing their employees with sports facilities and education regarding regular exercise and sleeping more than 7 hours.